Plasma Fatty Acid Binding Protein 4 and Risk of Sudden Cardiac Death in Older Adults - Luc Djoussé; Marlena Maziarz; Mary L. Biggs; Joachim H. Ix; Susan J. Zieman; Jorge R. Kizer; Rozenn N. Lemaitre; Dariush Mozaffarian; Russell P. Tracy; Kenneth J. Mukamal; David S. Siscovick; Nona Sotoodehnia (Cardiology Research and Practice)
Although fatty acid binding protein 4 (FABP4) may increase risk of diabetes and exert negative cardiac inotropy, it is unknown whether plasma concentrations of FABP4 are associated with incidence of sudden cardiac death (SCD). We prospectively analyzed data on 4,560 participants of the Cardiovascular Health Study. FABP4 was measured at baseline using ELISA, and SCD events were adjudicated through review of medical records. We used Cox proportional hazards to estimate effect measures. During a median followup of 11.8 years, 146 SCD cases occurred. In a multivariable model adjusting for demographic, lifestyle, and metabolic factors, relative risk of SCD associated with each higher standard deviation (SD) of plasma FABP4 was 1.15 (95% CI: 0.95–1.38), P=0.15. In a secondary analysis stratified by prevalent diabetes status, FABP4 was associated with higher risk of SCD in nondiabetic participants, (RR per SD higher FABP4: 1.33 (95% CI: 1.07–1.65), P=0.009) but not in diabetic participants (RR per SD higher FABP4: 0.88 (95% CI: 0.62–1.27), P=0.50), P for diabetes-FABP4 interaction 0.049. In summary, a single measure of plasma FABP4 obtained later in life was not associated with the risk of SCD in older adults overall. Confirmation of our post-hoc results in nondiabetic people in other studies is warranted.